THE PRINCIPLE OF JUSTICE IN SUPREME COURT DECISION NO. 675 K/PDT.SUS-PHI/2025 FOR WORKERS - Imanuela, Pricillia; Rasji (Awang Long Law Review, 2025)
This study aims to analyze the effectiveness of Judicial Review as a substantive corrective legal remedy against Supreme Court cassation decisions that fail to grant the full scope of workers’ normative entitlements in cases of unilateral termination of employment, as well as to identify the critical barriers that limit workers’ access to such remedies. This research employs a normative juridical method with a statutory and case-study approach, focusing on a critical analysis of Supreme Court Decision No. 675 K/Pdt.Sus-PHI/2025. The findings conclude that Judicial Review holds significant potential as a safeguard for justice in correcting discrepancies in cassation decisions that grant only a minimal portion of workers’ rights. However, this potential is hindered by two layers of constraints: regulatory uncertainty due to the absence of specific provisions on Judicial Review within the Law on Industrial Relations Dispute Settlement, and practical obstacles arising from the Supreme Court’s restrictive judicial posture combined with the high financial and temporal burdens imposed on workers. It is recommended that the Supreme Court issue a Supreme Court Regulation easing the requirements for Judicial Review for workers based on the favor laboris principle, in order to realise substantive justice that is prompt, simple, and cost-efficient.